Advancements in Real-Time Data Processing in Medical Research - Naveen Kumar Pedada (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Real-time data processing has revolutionized medical research by transforming how clinical investigations are conducted and analyzed. This article examines the evolution from traditional batch processing to instantaneous data analysis across the healthcare ecosystem. The article explores five key areas: the historical context and transformative potential of real-time processing; its application in clinical trials through electronic data capture and risk-based monitoring; artificial intelligence applications in drug discovery that have dramatically accelerated therapeutic development; breakthrough treatments enabled by continuous monitoring technologies; and global health implications with focus on infectious disease management and health equity. Ethical considerations, privacy concerns, and implementation challenges in resource-limited settings are also addressed, along with emerging technologies that promise to transform biomedical research and clinical practice further. The integration of real-time data processing represents a paradigm shift with profound implications for patient outcomes, healthcare resource allocation, and global disease eradication efforts.